1986
DOI: 10.1111/j.2042-7158.1986.tb04502.x
|View full text |Cite
|
Sign up to set email alerts
|

Effects of various cephem antibiotics on ethanol metabolism and their structure-activity relations

Abstract: The effects of various cephem antibiotics and related compounds on ethanol metabolism were studied in association with their chemical structures. In rats, cefoperazone, cefbuperazone, cefamandole, latamoxef, cefmetazole, cefotetan, cefmenoxime and cefminox which have the [(1-methyl-1H-tetrazol-5-yl) thio] methyl group at position 3 of the cephem ring caused a significant increase in the blood acetaldehyde concentration. In the last three compounds, disulfiram-like activity was less potent than that evaluated i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
1
0
1

Year Published

1987
1987
2020
2020

Publication Types

Select...
4
2
1

Relationship

0
7

Authors

Journals

citations
Cited by 9 publications
(2 citation statements)
references
References 12 publications
0
1
0
1
Order By: Relevance
“…In the last compounds disulfiram like-activity is explained by chemical structure or more precisely by the presence methyltetrazolethiol side-chain at position 3 of the cephem ring (like in cefoperazone, cefamandole, cefotetan). In the case of cefazolin, cephalosporin with 1Htetrazol group at position 7 of the cephem ring, the study published in 1986 showed that it also had disulfiram-like activity 21 . However, other experimental studies demonstarted that cefazolin did not significantly influence on alcohol metabolism 22,23 .…”
Section: Discussionmentioning
confidence: 99%
“…In the last compounds disulfiram like-activity is explained by chemical structure or more precisely by the presence methyltetrazolethiol side-chain at position 3 of the cephem ring (like in cefoperazone, cefamandole, cefotetan). In the case of cefazolin, cephalosporin with 1Htetrazol group at position 7 of the cephem ring, the study published in 1986 showed that it also had disulfiram-like activity 21 . However, other experimental studies demonstarted that cefazolin did not significantly influence on alcohol metabolism 22,23 .…”
Section: Discussionmentioning
confidence: 99%
“…Και οι τέσσερις αυτές κεφαλοσπορίνες, αναφέρεται πως σε συνδυασμό με οινόπνευμα προκαλούν «αντίδραση τύπου δισουλφιράμης», η οποία έχει αποδοθεί στην αναστολή της ηπατικής ALDH και στη συνεπακόλουθη αύξηση των επιπέδων της ακεταλδεϋδης στο αίμα (Reeves & Davies, 1980;Neu & Prince, 1980;Portier et al, 1980;Yamanaka et al, 1983). Μάλιστα, φαίνεται πως η αναστολή που προκαλούν στο ένζυμο οι κεφαλοσπορίνες αυτές, οφείλεται σε μία 1-μέθυλο-5θειοτετραζολική πλευρική ομάδα στη θέση -3 ή σε μία 1Η-τετραζολική ομάδα στη θέση -7 του διϋδροθειαζινικού δακτυλίου του μορίου τους, καθώς οι ομάδες αυτές βρέθηκε να αναστέλουν in vivo την ALDH σε επίμυες (Kamei et al, 1986). 5) Γκριξεοφουλβίνη: ανήκει στην κατηγορία των αντιμυκητιασικών, με κύριες ενδείξεις τις βαριές μυκητιάσεις του δέρματος, του τριχωτού της κεφαλής και των ονύχων, από επιδερμόφυτα, μικρόσπορα και τριχόφυτα, όταν τα τοπικά αντιμυκητιασικά είναι ακατάλληλα (Εθνικό Συνταγολόγιο, 2003).…”
Section: φαρμακευτικοί παράγοντες γνωστοί για την πρόκληση «αντίδρασης τύπου δισουλφιράμης»unclassified